Antibacterial Activity Testing Propionibacterium acnes Combination of 70% Ethanol Extract of Starfruit Leaves (Averrhoa bilimbi L.) and Jarak Pagar Leaves (Jatropha curcas L.) - Putri, Tarisya Anilya Dwi; Yuliana, Agnes; Krismayadi, Krismayadi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Acne is an inflammation accompanied by blockage of oil gland ducts that gather and cause blackheads. The onset of acne can be caused by the bacterium Propionibacterium acnes. Flavonoid compounds and tannins contained in star fruit leaves and jatropha leaves can be used as antibacterials. Both extracts from the plant can be combined to achieve antibacterial effects that can be used as an alternative to acne treatment. The purpose of this study was to determine the antibacterial activity of star fruit leaf extract and jatropha leaf and determine the optimal concentration resulting from the antibacterial activity of the extract combination. The method used is experimental and antibacterial tests in vitro. The results of antibacterial tests on the combination of jatropha leaf extract and star fruit leaf extract against P. acnes had the most optimal average inhibitory zone of 9,642 mm with a ratio of 1:2 at a concentration of 10%.